The Walfare of Local Farmers, Rice Price Policy, and Distribution Process in Improving Food - Nuzul Rahayu Nita (International Consortium of Education and Culture Research Studies, 2017)
Food security is an integrated food economy system consisting of various subsystems (Suryana, 2003). Food security contains at least two basic elements, namely the availability of adequate food and the accessibility of the community to adequate food, where both elements are absolutely fulfilled in order to achieve the health and welfare of society. This paper presents a review of grain price policy and distribution access in analyzing the welfare of local farmers and their impact on food security in Tanggulangin, Indonesia. This research uses descriptive method approach. Using interview with source from food security departement. The results of the analysis indicate that the food welfare factors do not have a significant effect on food security in the surplus food sub-district. While access factor and also policy of food price policy give significant influence to food security and welfare of farmers in subdistrict with surplus of food in 2014. The result of this study are important to see the developtment food security in surplus food security areas.